Fennoscandian tree-ring anatomy shows a warmer modern than medieval climate - Björklund Jesper; Seftigen Kristina; Stoffel Markus; Fonti Marina V.; Kottlow Sven; Frank David C.; Esper Jan; Fonti Patrick; Goosse Hugues; Grudd Håkan; Gunnarson Björn E.; Nievergelt Daniel; et al. (Zenodo, 2023)
This repository contains the Matlab scripts used in the article Björklund et al 2023. Fennoscandian tree-ring anatomy shows awarmer modern than medieval climate. Nature.DOI 10.1038/s41586-023-06176-4URL: https://www.nature.com/articles/s41586-023-06176-4 Investigators:Jesper Björklund, Kristina Seftigen, Markus Stoffel, Marina V. Fonti, Sven Kottlow, David C. Frank, Jan Esper, Patrick Fonti, Hugues Goosse, Håkan Grudd, Björn E. Gunnarson, Daniel Nievergelt, Elena Pellizzari, Marco Carrer & Georg von Arx The Workflow folder Workflow_Björklund_etal_2023_Nature.zip contains all the necessary notes, codes and data to reproduce Main Figures 2, 3, 4 and Extended Data Figures belonging to the Article. The raw data and most of the processed data can be accessed directly through Source Data, and underlying data files to reproduce analyses and figures, or through the Matlab codes calling source data and raw data included in the folder. The Matlab working environment is necessary to operate the Matlab codes. Workflow folder also contains a number of Matlab functions necessary to run the codes some of which are created by Jesper Björklund and some of which are created by other researchers published online. The Matlab codes are numbered from 1-19 according to the workflow order. Codes 1-6 must be run in order to obtain required data to run the subsequent figure codes 7-19. For more information contact Jesper Björklund at jesper.bjoerklund@wsl.ch